Spontaneously growing plants on revegetation sites of former coal mine in South Kalimantan Province, Indonesia - MOCHAMAD ARIEF SOENDJOTO; MAULANA KHALID RIEFANI; DIDIK TRIWIBOWO; FAZLUL WAHYUDI; DODIK CHOIRUN; YUDHA PAHING PERDANA (Society for Indonesian Biodiversity, 2023)
Abstract. Soendjoto MA, Riefani MK, Triwibowo D, Wahyudi F, Choirun D, Perdana YP. 2023. Spontaneously growing plants on revegetation sites of former coal mine in South Kalimantan Province, Indonesia. Biodiversitas 24: 1610-1620. Plants that grow and develop on the revegetation sites of post-coal mining are not only plant species that are intentionally planted, but also those that grow spontaneously. The aim of the research was to inventory plant species that grow spontaneously on revegetation sites of former coal mine sites in South Kalimantan Province and to analyze their presence mechanism and maintenance practices. Vegetation sampling was conducted on the plots established along the path with the size of each plot was 2 x 2 m2. All plants herbs (except grasses) and seedlings (shrubs, bushes, lianas and trees) within the plots were recorded and the vegetation composition was analyzed using Important Value Index as the parameter. Vegetation was monitored for 5 periods from 2018 to 2022 at the revegetation sites of two different planting years, i.e. 2016 and 2017. At Site-2016, 60 species belonging to 22 plant families were found and 71.67% of them grew spontaneously, while at Site-2017 there were 58 species belonging to 22 plant families and 70.69% of them were plants that grew spontaneously. Spontaneously growing species varied not only by location, but also by monitoring period. They are present at revegetation sites through seed dispersal mechanisms facilitated by natural activities (such as animals, wind, and water) as well as human activities. There are several management practices to facilitate vegetation succession, one of which is through spraying herbicides of weeds and invasive understorey species.